2019
DOI: 10.1017/s1366728919000610
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of clitics and articles to bilingual effects in typically developing Spanish–English bilingual children

Abstract: This study examines bilingual effects in Spanish–English bilingual children with good maintenance of the minority language. The present study compares the performance of a group of Spanish-monolingual children (MON; n = 30) with two groups of Spanish-speaking bilingual children (Low English proficiency group: LEP; n = 36; High English proficiency group, HEP; n = 36) on the elicited productions of Spanish articles and object clitics. Our results suggest that children with LEP performed significantly lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 49 publications
1
12
0
2
Order By: Relevance
“…Previous research has demonstrated that bilingual children omit direct objects more than monolingual children do (Castilla-Earls, Restrepo, Pérez-Leroux, Gray, Holmes, Gail & Chen, 2016;Castilla-Earls, Pérez-Leroux, Martinez-Nieto, Restrepo & Barr, 2020;Pirvulescu et al, 2014;Sánchez, 2003). This bilingual effect has been explained as the result of restricted input and lexical development (Pérez-Leroux et al, 2018;Pirvulescu et al, 2014;Shin, 2022).…”
Section: Spanish-english Bilingual Children's Direct Object Typesmentioning
confidence: 97%
“…Previous research has demonstrated that bilingual children omit direct objects more than monolingual children do (Castilla-Earls, Restrepo, Pérez-Leroux, Gray, Holmes, Gail & Chen, 2016;Castilla-Earls, Pérez-Leroux, Martinez-Nieto, Restrepo & Barr, 2020;Pirvulescu et al, 2014;Sánchez, 2003). This bilingual effect has been explained as the result of restricted input and lexical development (Pérez-Leroux et al, 2018;Pirvulescu et al, 2014;Shin, 2022).…”
Section: Spanish-english Bilingual Children's Direct Object Typesmentioning
confidence: 97%
“…Romance languages have also been in contact with many languages across the globe, providing abundant opportunities to study bilingualism and the outcomes of language contact. Studies of bilingual children who speak at least one Romance language abound in the fields of bilingual and child heritage language acquisition, and have informed our understanding of how factors such as input, language dominance, and cross-linguistic influence shape the development of grammar during childhood (e.g., Castilla-Earls et al 2020, Cuza 2016, Cuza & Pérez-Tattam 2016, Fernández Fuertes & Liceras 2018, Montrul & Potowski 2007, Pérez-Leroux et al 2018, Pirvulescu et al 2014, Sánchez 2019, Serratrice 2018, Shin et al 2019, among many others). Research on Spanish in Latin America continues to generate new knowledge regarding the ways in which language contact results in innovative grammatical constructions and innovations in language use patterns (e.g., Escobar 2018, Mayer & Sánchez 2017, Vallejos 2019.…”
Section: Isogloss: What Do You Think Are the Most Important Contributions Of Romance Linguistics To Linguistic Theory In General?mentioning
confidence: 99%
“…Sin importar la perspectiva del estudio de los hhs, el consenso general es que en la lengua de herencia (lh) los hhs difieren de los hablantes monolingües (Benmamoun et al, 2013a(Benmamoun et al, , 2013bCastilla-Earls, Pérez-Leroux et al, 2019;Montrul, 2008Montrul, , 2016Silva-Corvalán, 2016). Por otro lado, estudios enfocados en el desarrollo de la lengua mayoritaria han encontrado que el desarrollo del inglés también difiere en los hablantes monolingues (Jacobson & Schwartz, 2005).…”
Section: Introductionunclassified
“…De forma general, el desarrollo del lenguaje en niños bilingües se caracteriza por alteraciones en el tiempo y en la adquisición de ciertas estructuras en comparación con los monolingües. A esto se le conoce como efectos del bilingüismo (Castilla-Earls, Restrepo et al, 2016;Castilla-Earls, Pérez-Leroux et al, 2019;Pirvulescu et al, 2014) o efectos cuantitativos (Meisel, 2007).…”
Section: Introductionunclassified